PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDS YKPP SUNGAI PAKNING - Koderi Koderi; Syahrilfudin Syahrilfudin; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problems in this study is the lack of student learning outcomes, especially in Maths. According to this problem, the researchers have been conducting research to improve student learning outcomes by implementing cooperative learning methods make a match. The type of research is classroom action research (PTK), and carried out in two cycles. While the subject of this study is the fourth grade students SDS YKPP Sungai Pakning school year 2015/2016 the number of students 32 people. Results from this study is the increase in the activity of the teacher, student activities, and student learning outcomes. At the first meeting of the first cycle, the percentage of teachers activity of 45.83% with less category, at the second meeting increased to 54.17% with less category. At the first meeting of the second cycle of 70.83% the percentage of teachers with enough categories, and at the second meeting increased further to 87.50% in both categories. At the student activity also increased, namely in the first cycle of the first meeting with a percentage of 50.00% with less category, and at the second meeting increased to 62.50% with less category. At the first meeting of the second cycle percentage is 75.00% with enough categories, and at the second meeting increased to 91.67% with the category very well. On student learning outcomes also increased with an average score of students before action is 63.86, the first cycle increased to 74.52. And on the second cycle increased again to 81.39.Keywords: Cooperative Learning Model Make A Match, Math Learning Outcome